Farmers Experiences with Pluralistic Extension System in Promotion of Conservation Agriculture in Chinguluwe Epa of Salima District, Malawi - Mary Magombo, Mphatso (Journal of Agricultural Extension Management, 2018)
Malawi’s current extension policy supports pluralism and advocates responsiveness to farmer demands. This article therefore investigates the experiences of male and female farmers in selected sections with pluralistic extension in promotion of conservation agriculture (CA). The key question addressed in this research is what changes has pluralistic extension system made in case of the farmers practicing conservation agriculture. Within a case study approach, four sections were purposively selected for in-depth qualitative analysis of available services and farmers’ experiences. Focus group discussions were held separately with male and female farmers and key informants followed by semi-structured interviews with 150 farming households. The findings have revealed that few farmers appreciate having access to a variety of sources of technical advice in conservation agriculture. However, most service providers continue to dominate and dictate what they offer such that most of the responses are not relevant to address farmers expressed needs. In addition, the study has revealed that poor coordination between service providers limits exploitation of potential synergies amongst actors. As a recommendation therefore, service providers can adapt their approach to engage farmers in discussion of their needs and work collaboratively to address them. At a system level, institutions that have a coordination function can play a more dynamic role in brokering interaction between providers and farmers to ensure coverage and responsiveness.